TEOLOGI KONSEP USWAH HASANAH ROSULULLAH - Ike Nilawati Rohaenah; Andewi Suhartini; Nur Wadjah Ahmad (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2020)
Uswatun Hasanah is the Pattern of Life of the Prophet Muhammad. The main condition in setting a good example is to have noble morals. In education that ethics is a teaching of nobility. An individual's actions can be measured through ethics, humans can determine whether he can be accepted by others or rejected. Verily, I was sent (by Allah) to perfect noble morals. The study used the Book Literacy methodology. The purpose of this study was to discuss the moral behavior of Rosullullah Saw (Uswah Hasanah). The result of this research is that Rasulullah has the characteristics of Shiddiq (True), Fathanah (Intelligent), Amanah (Can be trusted), Tablig (Convey), Istiqomah (Consistent). The importance of this research is because Muslims are far from imitating the morals of Rosulullah Saw